Engagement with “Real Readers and James Frey’s A Million Little Pieces: Autofiction as a Reading Strategy and the Mediating Role of Authenticity” by Melina Ghasseminejad - Zetterberg-Nielsen, Henrik (Narrative Works, 2025)
It is an honor for me to have been invited to engage with Melina Ghasseminejad’s research as presented in the article on a topic and on theoretical questions very important to me, but here addressed in completely new ways. The turn to real readers in the context of autofiction and of fictionality theory is a new and major step, and one that has obviously required a great deal of effort methodologically, theoretically, and in terms of conducting the interviews in fruitful ways. This is a very commendable path to explore. In the following I will briefly focus on questions about the relation between lies, truth, and fictionality and between honesty and dishonesty, deception and non-deception. Next, I will examine why it matters – especially in the context of real readers as opposed to underlying structures or theoretical abstractions. Finally, I will engage with the author’s overarching conclusions and findings and their importance.